From an amvivalence in identity formation to the dichotomy in interest formation - İncekara, Rahmi; Güçyetmez, Ferdi Tayfur (Nişantaşı Üniversitesi, 2020)
While becoming a member of international community on the one side, and insisting on preserving values and norms of Hobbesian culture on the other side, sovereigns face an intricate dilemma from within domestic inhibitions in conducting integration with the norms from outside. Dichotomy in interest formation with respect to foreign policy relations with the others reveals the fact that no mature international collective identity is possible since there already exists a serious problem, or paradox, in identity formulation from within, considering the complex interdependence feature of globalization and sub-nation identity in contradiction with state identity within the Westphalian territory. The underlying cause of problems in Lockean interest formation in foreign policy is the polarizing domination of Hobbesian culture in domestic politics. Holding constant the unit of analysis as state, interest and identity are the dependable variables, the interaction (socialization) is independent variable in this article. Theoretically, such a strong argument based upon Wendt’s approach to the relations of behavior, interest and identity in respective; States organize their actions by some interests defined by their identity. We will try to come to the conclusion by defending the importance of the phenomenon of identity in the process in which global powers have a voice in the economy and that the powers that do not have international organizations can never have an economic hegemonic measure.

Bir tarafta uluslararası topluluğun bir üyesi olurken, diğer tarafta Hobbes kültürünün değerlerini ve normlarını korumakta ısrar eden egemenler, dışarıda normlarla entegrasyonun gerçekleştirilme çabasında olurken, içerde ise engellemelerle karşı karşıyadır. Küreselleşme ile ekonomik altyapının karşılıklı bağımlılığı dış politika ilişkilerinde ülke çıkarlarına ters düşmekte ve ikilem oluşturabilmektedir. Ülkelerin karşılıklı bağımlılığı göz önünde bulundurarak kendi ulus kimliğini üstte tutması ve uluslararası kuruluşlarla iş birliği yapmasının mümkün olmadığını söylemesi küreselleşme adına bir paradoks oluşturacaktır. Bu noktada çatışma kuramları devreye girmekte, dış politikada ‘Lock’çu faiz oluşumundaki sorunların altında yatan neden, ‘Hobbes’çu kültürünün iç politikada kutuplaştırıcı hakimiyetidir. Bu karşılıklı bağımlılıkların ve paradoksun analizini bu makale içerisinde inceleyeceğiz. Burada devlet ve kimlik olgusu bağımlı değişkenler olurken, etkileşim (sosyalleşme) ise bağımsız değişken olacaktır. Teorik olarak, Alexander Wendt’in teorik davranışını ele aldığımız çalışma, kimlik ilişkileri ve yaklaşımlarının güçlü bir argüman olduğunu; Devletlerin eylemlerini gerçekleştirken kimlikleriyle tanımlanan bazı grupların çıkarlarına göre işleri organize ettiğinden bahsedeceğiz. Küresel güçlerin ekonomi üzerinde söz sahibi olduğu süreçte kimlik olgusunun önemi ve uluslararası kuruluşlara sahip olmayan güçlerin hiçbir zaman tam anlamı ile ekonomik hegemon ölçüsüne sahip olamayacağı tezini savunarak sonuca varmaya çalışacağız.Keywords: Keyword 1, keyword 2, keyword 3 (keywords should not exceed 3- 5 words)
Kimlik formasyonundaki belirsizlikten çıkar formasyonundaki zıtlıklara
Keywords: Economy; Economic Dependence; Identity; Lockean Practice; Hobbesian Mind; Ekonomi; Ekonomik Bağımlılık; Kimlik; Lockean Uygulaması; Hobbes Düşüncesi